THE INFLUENCE OF MARKET ORIENTATION, PRODUCT QUALITY AND DIGITAL PROMOTION ON PURCHASING DECISIONS IN THE FISHERY BUSINESS "MUTIARA FISH", UMBULSARI DISTRICT, JEMBER REGENCY - Firmansyah, Achmad Faiz Hilman; Hermawan, Haris; Rahayu, Jekti (Dynamic Management Journal, 2025)
The increasingly tight business world competition, businesses must find the best way to market their goods. Every business in all categories must be sensitive to every change and put customer satisfaction as the main goal. This research aims to determine and analyze the influence of market orientation, product quality and digital promotion on purchasing decisions in the "mutiara fish" fishing business. This type of research uses quantitative methods with a sample size of 100 respondents and uses non-probability sampling techniques with purposive sampling techniques using data collection techniques in the form of questionnaires to respondents. The data analysis technique for this research uses instrument testing, classical assumptions, multiple linear regression, hypotheses and coefficient of determination. The analysis results obtained show that market orientation, product quality and digital promotion have a partially positive and significant effect on purchasing decisions for Mutiara Fish products, the results of the R2 Determination Coefficient test with an influence contribution level of 0.634 or 63%.